Suprahepatic Inferior Vena Cava and Internal Jugular Vein Thrombosis: A Rare Complication Of Pancreatitis: Case Report - Apurv N Patel; Meghna M Patel; K R Patel (International Journal of Medical Research and Review, 2014)
Vascular thrombosis of portal veins and splenic vein due to pancreatitis has been described. Involvement of suprahepatic inferior vena and internal jugular vein is a rare complication of acute pancreatitis. Here we report a case of suprahepatic inferior vena cava thrombosis and internal jugular vein thrombosis in an alcoholic patient presented with acute pancreatitis.